2014
DOI: 10.1371/journal.pone.0094089
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of Secretory and Endocytic Organelles in Giardia lamblia

Abstract: Giardia lamblia is a flagellated protozoan enteroparasite transmitted as an environmentally resistant cyst. Trophozoites attach to the small intestine of vertebrate hosts and proliferate by binary fission. They access nutrients directly via uptake of bulk fluid phase material into specialized endocytic organelles termed peripheral vesicles (PVs), mainly on the exposed dorsal side. When trophozoites reach the G2/M restriction point in the cell cycle they can begin another round of cell division or encyst if the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 74 publications
(145 reference statements)
2
23
0
Order By: Relevance
“…lamblia mitosomes remain the smallest known and least characterized MROs. Identification of protein components using shotgun proteomic analysis of enriched mitosome preparations has proven challenging primarily due to difficulties in isolating sufficient amounts of contaminant-free organelles [33,48]. Extensive sequence divergence prevents identification of organelle proteins via homology-based searches; a case in point is Gl TOM40 whose sequence degeneration is so extensive that the identification of orthologues in Giardia , Entamoeba or Spironucleus remains tentative despite the constraints imposed by the beta barrel structure of these mitochondrial porins [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…lamblia mitosomes remain the smallest known and least characterized MROs. Identification of protein components using shotgun proteomic analysis of enriched mitosome preparations has proven challenging primarily due to difficulties in isolating sufficient amounts of contaminant-free organelles [33,48]. Extensive sequence divergence prevents identification of organelle proteins via homology-based searches; a case in point is Gl TOM40 whose sequence degeneration is so extensive that the identification of orthologues in Giardia , Entamoeba or Spironucleus remains tentative despite the constraints imposed by the beta barrel structure of these mitochondrial porins [44].…”
Section: Discussionmentioning
confidence: 99%
“…lamblia , conventional data mining strategies for identification of mitosome proteins based on homology-based in silico searches fall short [26,28,32,43,44,45,46,47]. Moreover, classical, organelle enrichment-based proteome analyses approaches have had only limited success owing to the small size of the organelles and the omnipresence of contaminating endoplasmic reticulum (ER) and cytoskeleton elements in mitosome fractions [33,48,49]. …”
Section: Introductionmentioning
confidence: 99%
“…Most of the proteomic studies so far reported for Giardia were undertaken in trophozoites undergoing encystation [10–12]. Only a few studies have focused on proteins secreted by Giardia and their role in the host-pathogen interaction [3, 13–15].…”
Section: Introductionmentioning
confidence: 99%
“…Deeper in the encystation process, we face a paradigm: is there a Golgi-like structure in Giardia? Some authors claimed that during the encystation process, the ESVs assume some Golgi characteristics [13].…”
Section: Giardia and Giardiasismentioning
confidence: 99%